Second Attempt of Cabergoline Withdrawal in Patients with Prolactinomas after a Failed First Attempt: Is it Worthwhile? - Vilar, Lucio; Albuquerque, José Luciano; Gadelha, Patrícia Sampaio; Rangel Filho, Frederico; Siqueira, Aline Maria C.; da Fonseca, Maíra Melo; Viana, Karoline Frazão; Gomes, Barbara Sales; Lyra, Ruy (Frontiers in Endocrinology, 2015)
Successful discontinuation of cabergoline (CAB) treatment has been reported in 31 to 74% of prolactinomas patients treated for at least two years. In contrast, it is not well established whether CAB therapy can be successfully withdrawn after a failed first attempt. This prospective open trial was designed to address this topic and to try to identify possible predictor factors. Among 180 patients with prolactinomas on CAB therapy, the authors selected those who fulfilled very strict criteria, particularly additional CAB therapy for at least 2 years, normalization of serum prolactin (PRL) levels following CAB restart, no tumor remnant > 10 mm, no previous pituitary radiotherapy or surgery; and current CAB dose ≤1.0 mg/week. Recurrence was defined as an increase of PRL levels above the upper limit of normal. A total of 34 patients (70.6% female) treated with CAB for 24-30 months were recruited. Ten patients (29.4 %) remained without evidence of recurrence after 24–26 months of follow-up. Twenty-four patients (70.6%) recurred within 15 months (75% within 12 months) after drug withdrawal and ~80% were restarted CAB. Median time to recurrence was 10.5 months (range, 3–15). Despite overlapping values, non-recurring patients had significantly lower mean PRL levels before withdrawal. Moreover, the recurrence rate was lower in subjects without visible tumor on pituitary MRI than in those with small remnant tumor (60 vs. 79%), though the difference was not statistically significant (P= 0.20). No other characteristic could be identified as a predictor of successful CAB discontinuation. In conclusion, a second attempt of CAB withdrawal after 2 additional years of therapy may be successful, particularly in patients with lower PRL levels and no visible tumor on pituitary MRI. Close monitoring of PRL level is mandatory, especially within the first year after withdrawal, where most recurrences are detected.